2011
DOI: 10.2320/matertrans.m2010272
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Concentration Dependence of Thermoelectric Properties of β-Rhombohedral Boron Prepared by Spark Plasma Sintering

Abstract: Samples of 1 at% metal (Al, Co, Cr, Cu, Mo, Nb, Ni, Ru, Si, V, W, Zr)-doped -rhombohedral boron (-boron) were prepared by spark plasma sintering and their thermoelectric properties were examined in the temperature range from 353 K to 1073 K. It was found that V-dopedboron exhibited the largest dimensionless figure of merit (ZT value). The V concentration dependence of the thermoelectric properties ofboron was investigated. We discuss the effects of V doping into -boron and the precipitation of a second phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Though various higher-boride thermoelectric materials have been developed to date, there are few report about ntype higher-boride materials [14e16]. Kim and Kimura reported that b-rhombohedral boron exhibited a change of Seebeck coefficient between positive and negative along with vanadium doping [17]. Maruyama et al reported to control of sign of Seebeck coefficient on YAlB 14 the structure of which is similar to that of AlMgB 14 [18] by controlling metal occupancy [15].…”
Section: Introductionmentioning
confidence: 96%
“…Though various higher-boride thermoelectric materials have been developed to date, there are few report about ntype higher-boride materials [14e16]. Kim and Kimura reported that b-rhombohedral boron exhibited a change of Seebeck coefficient between positive and negative along with vanadium doping [17]. Maruyama et al reported to control of sign of Seebeck coefficient on YAlB 14 the structure of which is similar to that of AlMgB 14 [18] by controlling metal occupancy [15].…”
Section: Introductionmentioning
confidence: 96%
“…However, most B 12 icosahedral cluster solids have comparatively high thermoelectric properties at a high temperature, making them promising high-temperature thermoelectric materials. However, most B 12 icosahedral cluster solids are p-type materials and the development of an n-type material to create a pair is desirable [ 16 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding elemental boron, the structure of βrhombohedral (β-rh) B (space group m R3 ) [7][8][9][10][11] has been extensively studied with respect to its ability to accommodate interstitially different kinds of foreign atoms [12][13][14]. It has been shown that metal doping into β-rh B can control the bonding nature in and between the clusters, delivering variation of physical properties such as electrical and thermal conductivities and Seebeck coefficient [13,[15][16][17][18][19][20]. The interstitial doping of β-rh B by certain 3d-metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…V, Cr, Fe, Ni, Cu) led to negative values of TE power in the originally p-type semiconducting material in certain temperature ranges [13,21]; the structural and electronic properties of some solid solutions (i.e. V:B, Fe:B, Cu:B) have been consistently studied by different research groups [13,15,22,23].…”
Section: Introductionmentioning
confidence: 99%